Synthesis of 2‐(2‐Hydroxyaryl)‐4H‐benzo[e][1, 3]oxazin‐4‐ones by Palladium‐Catalyzed C(sp2)−H Hydroxylation via Electro‐chemical Oxidation. Issue 12 (23rd April 2020) - Wu, Hongfeng; An, Qi; He, Chaoyin; Fan, Xiaodong; Guo, Weihao; Zuo, Minghui; Xu, Chunzhao; Guo, Rui; Chu, Wenyi; Sun, Zhizhong
Abstract: An electrochemical direct ortho ‐hydroxylation of 2‐aryl‐4 H ‐benzo[ e ][1, 3]oxazin‐4‐ones was developed with Pd(OAc)2 as catalyst, oxazine ring as a directing group and Oxone as the hydroxylation reagent. A series of hydroxylation products were obtained under mild conditions, and the yields were from medium to good. This method is characterized by good functional group tolerance and a wide range of substrates. More importantly, use anodic oxidation to avoid the use of potentially toxic and polluting oxidants. A gram‐scale direct electrochemical hydroxylation of 2‐phenyl‐4 H ‐benzo[ e ][1, 3]oxazin‐4‐one was performed, and the hydroxylation product was applied to synthesize the drug deferasirox. In addition, the single crystal of 2‐(2‐hydroxyphenyl)‐4 H ‐benzo[ e ][1, 3]oxazin‐4‐one was obtained and determined by X‐ray diffraction. Finally, the reaction mechanism was proposed and verified by cyclic voltammetry (CV). This protocol also provides an alternative electrochemical hydroxylation methodology for the functionalization of molecules. Abstract :